International legal regulation of the rights of persons with disabilities: problems of formation and development - Maidanik, Serhii (Problems of legality, 2021)
At the level of international legal regulation disability policy is currently one of the priority areas. However, such attention to the international legal protection of the rights of persons with disabilities has not always been the case, as the problems of persons with disabilities have long remained unnoticed by the international community. Rare attempts to improve the situation with persons with disabilities were usually limited to medical protection and integration into the labor market, while the task of their full and actual involvement in public life was not even set. The article analyzes the preconditions, reasons and features of the evolution of the system of international legal protection of the rights of persons with disabilities, as well as examines the transformation of approaches to defining the concept of "disability" at the level of international law. The article defines the main stages of the formation of international cooperation in the field of protection of the rights of persons with disabilities. The article presents the results of the analysis of international legal documents on disability policy for the period from the beginning of the twentieth century to 2020.